2020
DOI: 10.1002/jeq2.20010
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of grazing management and buffer strips on phosphorus runoff from pastures fertilized with poultry litter

Abstract: Phosphorus (P) runoff from pastures can cause accelerated eutrophication of surface waters. However, few long‐term studies have been conducted on the effects of best management practices, such as rotational grazing and/or buffer strips on P losses from pastures. The objective of this study was to evaluate the long‐term effects of grazing management and buffer strips on P runoff from pastures receiving annual (5.6 Mg ha−1) poultry litter applications. A 14‐yr study was conducted on 15 small watersheds (0.14 ha)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
6
0
2
Order By: Relevance
“…Likewise, Anderson et al. (2020) found that increased runoff volumes led to significant increases in P runoff. Some studies have found that D b is not changed by tillage (Khaledian et al., 2012; Strudley et al., 2008), making it important to investigate interactions between soil management and other drivers of variance in D b .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, Anderson et al. (2020) found that increased runoff volumes led to significant increases in P runoff. Some studies have found that D b is not changed by tillage (Khaledian et al., 2012; Strudley et al., 2008), making it important to investigate interactions between soil management and other drivers of variance in D b .…”
Section: Resultsmentioning
confidence: 96%
“…Pilon et al (2017) found that increases in bulk density due to grazing from cattle resulted in higher runoff volumes from pastures and increased soil erosion. Likewise, Anderson et al (2020) found that increased runoff volumes led to significant increases in Water stable aggregate percentage (WSA), bulk density (D b ), permanent wilting point (θ PWP ), field capacity measured on repacked (θ FC_REPACK ) and intact (θ FC_INTACT ) cores, saturated hydraulic conductivity (K S ), and soil organic carbon (SOC) P runoff. Some studies have found that D b is not changed by tillage (Khaledian et al, 2012;Strudley et al, 2008), making it important to investigate interactions between soil management and other drivers of variance in D b .…”
Section: Response Of Indicators To Changes In Management Practicesmentioning
confidence: 99%
“…The field setup utilized 15 sloped and individually isolated manuresheds at the USDA-ARS Research Center in Booneville, Arkansas that have been previously described ( Pilon et al, 2017a , b , 2019 ; Anderson et al, 2020 ; Yang et al, 2021 ) ( Supplementary Figure S2 ). Three different agricultural conservation management practices were evaluated, including rotationally grazed (R), rotationally grazed with a buffer strip (RB), and rotationally grazed with a fenced riparian buffer (RBR).…”
Section: Methodsmentioning
confidence: 99%
“…Off-site movement of fertilizers and excess Microorganisms 2023, 11, 863 2 of 13 nutrient applications have led to issues such as soil salinity, heavy metal accumulation, water eutrophication, and accumulation of nitrates [8]. In grazed pastures, phosphorus runoff can cause water eutrophication in both coastal and freshwater systems [9]. Some coastal areas in the United States have already began implementing restrictions on fertilizer applications [10].…”
Section: Introductionmentioning
confidence: 99%